RELATIONSHIP BETWEEN STRONG GRAPHS, TWO-GRAPH, AND EQUIANGULAR LINES - Benedict Tanidi, Gregory
This Final Project discusses the relationship between strong graphs, two-graphs, and equiangular lines. A strong graph is a simple graph with a Seidel adjacency matrix that satisfies S2 = ?S, I, J?R. A two-graph is a mathematical object consisting of a finite set V and a finite set ? which contains a set with three members (triples) so that every set with four members of V contains an even triple in ?. Equiangular lines are lines that intersect at one point and every two different lines form the same acute angle. The results of this final project show that strong graphs and two-graphs have geometric properties that can be represented by equiangular lines.